2018
DOI: 10.1371/journal.pone.0197065
|View full text |Cite|
|
Sign up to set email alerts
|

Intraretinal changes in idiopathic versus diabetic epiretinal membranes after macular peeling

Abstract: IntroductionEpiretinal traction is not responsible only for epiretinal but also intraretinal changes. This study aims to describe structural and vascular intraretinal changes after macular peeling in idiopathic (iERM) vs diabetic ERM (dERM).MethodsWe conducted a prospective interventional study on forty-two eyes, 23 with iERMs and 19 with dERMs, undergoing ERM-ILM peeling. We performed SD-OCT preoperatively, 1 and 6 months postoperatively to assess central macular thickness (CMT), intraretinal cysts (IC) and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
(66 reference statements)
1
16
1
Order By: Relevance
“…The relative abundance of these components within each ERM case reflects the underlying etiology and the severity of the disease or its duration. In retinal ischemia or inflammation, such as in diabetic retinopathy or RVO, activation of Mu ¨ller cells induces the upregulation of glial fibrillary acidic protein and vimentin, with reactive gliosis and ERM formation [19,20]. As platelet-derived growth factor A (PDGF A) and VEGF receptors are expressed within ERM cells, intravitreal proangiogenic cytokines may accelerate ERM progression [21].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of these components within each ERM case reflects the underlying etiology and the severity of the disease or its duration. In retinal ischemia or inflammation, such as in diabetic retinopathy or RVO, activation of Mu ¨ller cells induces the upregulation of glial fibrillary acidic protein and vimentin, with reactive gliosis and ERM formation [19,20]. As platelet-derived growth factor A (PDGF A) and VEGF receptors are expressed within ERM cells, intravitreal proangiogenic cytokines may accelerate ERM progression [21].…”
Section: Discussionmentioning
confidence: 99%
“…Massin et al [25] explained that the partial recovery of macular morphology may be because of chronic deformation exerted by ERM traction and a certain degree of intra-retinal gliosis that prevents the macula from returning to its normal profile. Moreover, in a histological and immunohistochemical study by Romano et al [26], the authors demonstrated that chronic tractional stress exerted by idiopathic ERM could mechanically displace inner retinal layers centripetally and result in irreversible macular damage. Further, chronic tractional stress also acts on healthy Muller cells inducing reactive intra-retinal gliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have emphasized that persistent macular thickening after ERM surgery is more likely related to mechanical traction [25][26][27], the pull force on the retinal surface resulting in cytotoxic injury and vascular damage may be the other important cause of postoperative persistent macular thickening and cystoid changes in the macula. In a study by Frisina et al [7], the incidence rate of cystoid macular edema (CME) after ERM surgery was 12.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a significant correlation between BCVA at 6 months and RI at baseline and in particular, cases with higher baseline RI (indicative here of larger relaxation after surgery) reached a higher BCVA at 6 months ( Fig 5 ). Relaxation after surgery strictly depends on the grade of intra-retinal and epiretinal fibrosis, which is the result of the bond between Müller cells and ILM sustained by glial fibrillary acidic protein (GFAP) overexpression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%